Investigation of the evolution of arc: Azadegan magmatic rocks, north of Shahrekord, Sanandaj-Sirjan zone - Maryam Ahankoub; Farimah Ayati; madineh nazari (پترولوژی, 2021)
The magmatic complex of Azadegan, composed of basalt, andesitic basalt, andesite, gabbro and diorite, located 45 km northwest of Shahrekord and in the middle part of the Sanandaj-Sirjan zone.. The study rocks are dominated by plagioclase, olivine, pyroxene, hornblende as well as biotite and calcite as minor minerals. Geochemically, the rocks under study are calc-alkaline in nature and are characterized by Ce, Zr, Ba, and Sr depletion. Chondorite- normalized REE pattern illustrates LREE enrichment relative to HREE. Geochemical data of the studied samples indicate partial melting of the mantle source with the influence of fluids and sediments of the subducted crust during subduction. The ratio of Th/Yb (2-2.75) values are in consistent with those of the mature arc islands magma. Also, Ce /Y and Sr/Y ratios indicate the thickening of arc islands along with orogenic processes and maturation of arc islands in the study area. The for mentioned ratios also represent the thickness of crust up to 50 km., during orogenic processes at the end of subduction stages of the Neotethys.